Inventarisasi Kecenderungan Usaha-Usaha Ekonomi Produktif Fakir Miskin, Kendala-Kendala Yang Dihadapi Dan Upaya Solusinya - Fitriani, Rika; Fatimawati, Fitri (CV. ULIL ALBAB CORP, 2024)
This study, titled Inventory of Productive Economic Business Trends for the Poor, the Challenges Faced, and Solution Efforts, aims to identify the types of productive businesses managed by impoverished communities, understand the main obstacles they face in running these businesses, and propose actionable solutions. The main issue in this research is the low economic productivity among the poor due to various constraints, such as limited capital, market access, skills, and policy support. This research employs a descriptive qualitative method with a survey approach, in-depth interviews, and direct observation of productive business actors in several regions. Collected data is thematically analyzed to identify common patterns in business types, frequently encountered obstacles, and strategic recommendations that the government and relevant agencies can implement to improve economic sustainability. The study’s findings are expected to serve as a reference for designing more targeted and effective economic empowerment programs for the poor.